Relação materno filial no desempenho de ovinos Santa Inês no Noroeste do Paraná - Queiroz, Edicarlos Oliveira (2013)
This study aimed to evaluate the influence of summer and winter in the connection of the mother-infant and its effect on the labor duration, time to the ewe touch the lamb, the lamb stand up and occurrence of the first feeding. There were used 160 multiparous ewes Santa Ines, grazing on star grass (Cynodon nlemfuensis) and Tifton (Cynodon spp) in two treatments, summer: (80 sheep) and winter: (80 sheep). The sheep were evaluated from the start of delivery and lambs immediately after birth. The mother-infant bond during the summer occurred in at least 75 minutes. In winter, only took place between 150 and 190 minutes. The sheep calved in winter spent 4.48 % of the time without developing activities that demonstrate commitment to the formation of the mother-infant bond, while 0.18 % of the sheep calved in summer showed this behavior. During the summer the lambs spent 35.57 % of the time with no apparent activity, and 35.78 % in lying posture, while those born in winter remained without activities by 49.30 % and 52.32 % of the time in lying posture. The time to touch lambs was significantly lower, being of 20 seconds in summer and 45 seconds in winter. Lambs born in the summer took on average of 28 minutes to stand up and 78 minutes for those born in winter. The first feeding after birth for those born in the summer occurred on average of 63 minutes and those born in winter was of 167 minutes. The formation of the mother-infant bond has no interference from the summer and winter seasons. The summer season encourages the agility of sheep and lambs.